Quality Grading Evaluation of Overhead Insulated Wire Considering Specific Testing Conditions - XU Kan; YUAN Zhiwen; ZHANG Jinli; WANG Weitao (Journal of Harbin University of Science and Technology)
It is important to use material sampling to evaluate the quality of power equipment. In the equipment testing report, the simple judgement of qualified or unqualified is given to each testing index, which leads to the waste of a large number of testing data. In order to make more in-depth use of test data and understand the quality of equipment, based on adaptive grey clustering, combined with a number of testing indicators, a grading evaluation method for the overhead insulated wire is proposed. The consideration of test results under specific test conditions can simplify the evaluation system. The qualified power equipment quality can be classified into “ excellent ”and“ good”grades. . At the same time, the correlation analysis of test data under specific test conditions can simplify the evaluation index system. It deepens the utilization of the data in the equipment testing report, which is helpful for the testing personnel to understand the equipment quality more accurately and provides reference for the equipment procurement.